Psycho-collocations' in Malay: a Southeast Asian areal feature - Oey, Eric M. (2024)
Though mainland and insular Southeast Asia may be thought of in many ways as constituting a single regional entity — unified by common geographical conditions and by centuries of commercial and cultural contact — the languages of these two adjacent areas would appear, on the face of it, to have very little In common with each other. Indeed, typologically. they could hardly be more different — the languages of "Indochina" being predominantly (though not exclusively) isolating, monosyllabic (or tending to monosyllabicity) and tonal, whereas those of the "Malay Archipelago are polysyllabic, agglutinating and non-tonal. On this basis alone, it has always been assumed that they belong to entirely distinct stocks, with only marginal regional overlap.